2001
DOI: 10.1161/01.atv.21.5.844
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Oxidized LDL Is a Useful Marker for Identifying Patients With Coronary Artery Disease

Abstract: Abstract-Our aim was to determine the usefulness of circulating oxidized low density lipoprotein (LDL) in the identification of patients with coronary artery disease (CAD). A total of 304 subjects were studied: 178 patients with angiographically proven CAD and 126 age-matched subjects without clinical evidence of cardiovascular disease. The Global Risk Assessment Score (GRAS) was calculated on the basis of age, total and high density lipoprotein cholesterol, blood pressure, diabetes mellitus, and smoking. Leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
310
2
10

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 474 publications
(352 citation statements)
references
References 37 publications
(26 reference statements)
30
310
2
10
Order By: Relevance
“…The trend would be established on including a large number of subjects. Recent studies by Holvoet et al have shown that CAD patients had a higher level of circulating ox-LDL as compared to controls and the sensitivity of this circulating ox-LDL was 76% for cases of CAD (16). It has also been seen that patients with CAD have elevated titre of autoantibodies against ox-LDL as compared to healthy…”
Section: Controls (17)mentioning
confidence: 99%
“…The trend would be established on including a large number of subjects. Recent studies by Holvoet et al have shown that CAD patients had a higher level of circulating ox-LDL as compared to controls and the sensitivity of this circulating ox-LDL was 76% for cases of CAD (16). It has also been seen that patients with CAD have elevated titre of autoantibodies against ox-LDL as compared to healthy…”
Section: Controls (17)mentioning
confidence: 99%
“…A monoclonal antibody (4E6) against a conformational epitope in the ApoB-100 moiety of LDL was used (Holvoet et al, 1998(Holvoet et al, , 2001). The interassay coefficient variation was p7%.…”
Section: Standard Assaysmentioning
confidence: 99%
“…30, 31 We have shown that dyslipidemia in association with obesity is an independent predictor of circulating oxidized LDL in persons without clinical evidence of cardiovascular disease. 6 Because the assay for oxidized LDL in blood is based on a mouse monoclonal antibody, oxidized LDL cannot be measured directly in mouse blood. Previously, the titer of autoantibodies against MDA-modified LDL has been used as a proxy for oxidized LDL in mice.…”
Section: Oxidation Of Ldl and Macrophage Accumulationmentioning
confidence: 99%
“…However, the increased oxidative stress in obese dyslipidemic mice is in agreement with the increased oxidation of LDL in obese people. 6 …”
Section: Limitations Of the Studymentioning
confidence: 99%
See 1 more Smart Citation